Biodiesel production in the EU and Ukraine: current state and development prospects - Buliuk, Dmytro; Beyder, Elynor Yenia; Kuznietsova, Olena (Problems of Environmental Biotechnology, 2024)
The current state and prospects for the development of biodiesel production in the EU and Ukraine are considered